Goodman’s Extensional Isomorphism and Syntactical Interpretations - Polanski, Marek (THEORIA. An International Journal for Theory, History and Foundations of Science, 2009)
The aim of the present paper is to provide a model-theoretic explication of Goodman’s concept of extensional isomorphism. After some conceptual clarifications Goodman’s concept of isomorphy turns out to be closely related to some variant of set-theoretic definability and some variants of syntactical interpretability.